Komunikasi Antarbudaya Etnis Rohingya Dalam Upaya Eksistensi Diri di Kota Medan - Nora Maya Siregar (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
Issues of humanitarian crisis experienced by ethnic Rohingya back public interest. They have to leave the country and identified him as of asylum seekers. The search the asylum finally get them to the evacuation of hotel the rainbow of the city of Medan that is under the supervision of home detention immigration Medan. Research methodology used in this research is the method descriptive qualitative. The results of the study shows that in social intercourse that took place on ethnic Rohingya in the city of Medan, has resulted in the social process associative namely accommodation. Accommodation is the process of adjusting social occurring in a interaction. Communication and culture like two sides of the coin that cannot be separated. Communication individual influenced by the culture she had been learning as a kid. Therefore, ethnic Rohingya have to do adaptation to can keep existence her during years be in Medan. Forms example of an adaptation done by ethnic Rohingya in the city of Medan of language, food, clothing, way serve, and the state of the geographical.